The KIR2DL2/HLA-C1C1 Gene Pairing Is Associated With an Increased Risk of SARS-CoV-2 Infection - Hu, Song; Shao, Zuoyu; Ni, Wei; Sun, Pan; Qiao, Jialu; Wan, Hexing; Huang, Yi; Liu, Xiaolong; Zhai, Haoyang; Xiao, Mingzhong; Sun, Binlian (Frontiers in Immunology, 2022)
SARS-Cov-2 is the causative agent for the global COVID-19 pandemic; however, the interaction between virus and host is not well characterized. Natural killer cells play a key role in the early phase of the antiviral response, and their primary functions are dependent on signaling through the killer cell immunoglobulin-like receptor (KIR). This study measured the association between KIR/HLA class I ligand pairings and the occurrence and development of COVID-19. Blood samples from 257 COVID-19 patients were extracted and used to detect KIR and HLA-C gene frequencies using single strain sequence-specific primer (SSP) PCR. The frequency of these genes was compared among 158 individuals with mild COVID-19 infection, 99 with severe disease, and 98 healthy controls. The frequencies of KIR2DL2 (P=0.04, OR=1.707), KIR2DS3 (P=0.047, OR=1.679), and HLA-C1C1 (P<0.001, OR=3.074) and the KIR2DL2/HLA-C1C1 pairing (P=0.038, OR=2.126) were significantly higher in the COVID-19 patients than the healthy controls. At the same time, the frequency of KIR2DL3+KIR2DL2-/HLA-C1+Others+ was lower in COVID-19 patients than in healthy individuals (P=0.004, OR=0.477). These results suggest that the protective effect of KIR2DL3 against SARS-Cov-2 infection is related to the absence of the KIR2DL2 gene. This study found no correlation between the frequencies of these genes and COVID-19 pathogenesis. Global statistical analysis revealed that the incidence of COVID-19 infection was higher in geographic regions with a high frequency of KIR2DL2. Together these results suggest that the KIR2DL2/HLA-C1C1 gene pairing may be a risk factor for SARS-Cov-2 infection.